Qira’at dalam Tafsir Marah Labid: Studi Analisis Penggunaan dan Implikasi Qira’at atas Hukum - Moh. Fathurrozi (Jurnal Ulunnuha, 2023)
This article discusses the usage and implications of various qira'at (recitations) on istinbath al-hukm (deduction of legal rulings) in the tafsir "Marah Labid". The data source used is literature, which is analyzed using a descriptive-qualitative method on several verses that have different readings. The impact and function of these differences are then analyzed to produce a legal outcome. The aim is to understand how Sheikh Nawawi elucidates the qira'at and their implications on the law. In his work "Marah Labid", Sheikh Nawawi utilizes the differences in qira'at as a surgical tool to extract the meaning behind the Quranic verses. After analysis, several verses with different readings resulting in differences in istinbath al-hukm were found. First, the verse on purification: Al-Ma'idah 6 (washing/wiping the feet). Second, the worship-related verse: Al-Baqarah 125 (obligatory/sunnah to perform prayer at Maqam Ibrahim), Al-Baqarah 197 (perfection of the Hajj worship). Third, the verse on transactions: Al-Baqarah 282. Fourth, the family-related verse: Al-Baqarah 222 (the waiting period after menstruation). Fifth, the verse on crimes: Al-Baqarah 191 (committing murder in the Haram Mosque). From the research findings, it is concluded that differences in readings have an impact on the deduction of legal rulings.